HUBUNGAN KONTRASEPSI SUNTIK 3 BULAN DEPOMEDROXY PROGESTERON ASETAT (DMPA) DENGAN PERUBAHAN BERAT BADAN AKSEPTOR - Nur Hidayatul Ainiyah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective:Identifying Depo Medroxy Progesteron Asetat (DMPA) injection contraception to acceptors weight changing at SurabayaMethods: Design of this study is anlytic methid by purposive sampling. That sample used inthis study is partly of three month counted injection KB acceptor amounth 81 responden. This study is using data gathering dokumentation from acceptor card status and weight changingResults: X = 10,96 higher than X table = 7, 819, means Ho refused and H1 accepted there is relationship between applications of three month (DMPA) injection contraseption to acceptors weight changing.Conclusion:Healt funtionaries hoped to increase their information service. For DMPA injection contraception acceptors, they have to do balance activity and arrange their consumtions to keep balance weight so that injection KB acceptornstill as active acceptor